Waiting to start a business venture: Empirical evidence on the determinants and effects of wait time - Dirk Oberschachtsiek (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
In this paper, we study the intertemporal relations within two phases of the venture creation process based on data from administrative data sources. By distinguishing a pre- and post-period, we address two major issues: (1) we identify which factors make people wait to start a venture, and (2) we investigate the outcome of waiting on business longevity. Using survival modeling techniques, we find support for the hypothesis that regional economic conditions have a significant but complex effect on the delay of entries. Furthermore, we find that waiting is initially beneficial for self-employment duration but that this effect is not beneficial for longer periods of waiting.
Keywords: L27; M13; C41; 330; waiting time periods; self-employment; duration model; survival